2002
DOI: 10.1034/j.1600-079x.2002.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythm of glucose‐induced insulin secretion by isolated islets from intact and pinealectomized rat

Abstract: It is well known that pinealectomy induces in rats a diminished glucose tolerance, insulin resistance, a reduction in GLUT4 content in adipose and muscular tissues, a decrease in hepatic and muscular glycogenesis, impairment of glucagon action and an increase in blood pyruvate concentration. In addition, it has been shown that melatonin suppresses insulin secretion in several experimental conditions. The objective of the present study was to investigate the daily rhythm of glucose-induced insulin secretion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
27

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 42 publications
6
54
0
27
Order By: Relevance
“…Consistent experimental results in laboratory rats show that the absence of rhythmic release of melatonin in blood circulation leads to chronodisruption of functions associated with energy metabolism. In particular pinealectomy, suppressing the nocturnal rise in melatonin, disturbs the 24 h rhythm of plasma glucose concentration (la Fleur et al, 2001b) and eliminates the daily rhythm of glucose-induced insulin secretion (Picinato et al, 2002). In addition, impaired glucose tolerance, decreased adipose cell responsiveness to insulin and a reduction in GLUT4 content in muscle and adipose tissue have been reported after pinealectomy (Lima et al, 1998).…”
Section: Melatonin Rhythmmentioning
confidence: 99%
“…Consistent experimental results in laboratory rats show that the absence of rhythmic release of melatonin in blood circulation leads to chronodisruption of functions associated with energy metabolism. In particular pinealectomy, suppressing the nocturnal rise in melatonin, disturbs the 24 h rhythm of plasma glucose concentration (la Fleur et al, 2001b) and eliminates the daily rhythm of glucose-induced insulin secretion (Picinato et al, 2002). In addition, impaired glucose tolerance, decreased adipose cell responsiveness to insulin and a reduction in GLUT4 content in muscle and adipose tissue have been reported after pinealectomy (Lima et al, 1998).…”
Section: Melatonin Rhythmmentioning
confidence: 99%
“…First research studies revealed that secretion of melatonin was higher in women with both anorexia nervosa and bulimia than in the control groups [12]. However, experimental studies demonstrated increased insulin resistance, development of glucose intolerance, and weight gain in pinealectomised rats [13]. It was also shown that melatonin supplementation in animals with induced obesity had a positive effect on the secretion of leptin and adiponectin and on the level of glucose, cholesterol, and triglycerides [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the physiological functions of melatonin are, among other mechanisms, regulation of the circadian clock in the hypothalamic suprachiasmatic nucleus (SCN), seasonal reproduction, and inhibition of dopamine release from the retina (Morgan et al 1994;Vanecek 1998). Experiments with pinealectomized animals demonstrated that melatonin also plays a role in energy expenditure, body mass regulation, and insulin peripheral action and secretion (Margraf and Lynch 1993;Lima et al 1998;La Fleur et al 1999;Picinato et al 2002). It has been demonstrated that the biological effects of melatonin are mediated, at least in part, by specific high-affinity G protein-coupled receptors (GPCRs).…”
mentioning
confidence: 99%